2009
DOI: 10.1636/st08-32.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behavior of Chavesincola inexpectabilis (Opiliones, Gonyleptidae) with description of a new and independently evolved case of paternal care in harvestmen

Abstract: In this paper, we investigate the reproductive behavior of the gonyleptid Chavesincola inexpectahilis Soares & Soares 1946 (Heteropachylinae) and provide basic descriptive information about courtship, copulation, oviposition, and paternal care. Like most gonyleptids, males of C. inexpectahilis have a strong armature on the fourth pair of legs and use their spines and apophyses to fight other males and to repel them from their nesting sites. The mating pair interacts briefly before copulation, but the male touc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
1
25
2
1
Order By: Relevance
“…Considering that this behavior is not involved in pheromone releasing, this behaviour may be tactile in both of these species. Repeated touching of particular parts of the female body with legs or pedipalps during mating is common in harvestmen (Mora, 1990;Willemart et al, 2006Willemart et al, , 2009bNazareth & Machado, 2009;Requena & Machado, 2013; this study, both species), but this is the fi rst time that rubbing is reported. Tapping or rubbing different parts of the body of females may increase the chances of mating success for males at least in some spiders and scorpions (Eberhard, 1996;Huber & Eberhard, 1997;Peretti & Carrera, 2005).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Considering that this behavior is not involved in pheromone releasing, this behaviour may be tactile in both of these species. Repeated touching of particular parts of the female body with legs or pedipalps during mating is common in harvestmen (Mora, 1990;Willemart et al, 2006Willemart et al, , 2009bNazareth & Machado, 2009;Requena & Machado, 2013; this study, both species), but this is the fi rst time that rubbing is reported. Tapping or rubbing different parts of the body of females may increase the chances of mating success for males at least in some spiders and scorpions (Eberhard, 1996;Huber & Eberhard, 1997;Peretti & Carrera, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Such behaviour could be related to cryptic female choice, which increases the certainty of the paternity of the male (Eberhard, 1996). Finally, unlike in I. pustolosa and C. inexpectabilis, in which females terminated mating (Nazareth & Machado, 2009;Requena & Machado, 2013), both males and females of G. perlata may terminate mating by lowering the prosoma and pulling back.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations